Development of a Dental Care Nursing Service Model for School Students in Banda Aceh - Salfiyadi, Teuku (Poltekita: Jurnal Ilmu Kesehatan, 2025)
The prevalence of dental caries among children in Indonesia is alarmingly high, with 84% of children aged 5 to 12 years experiencing dental problems. This study aimed to evaluate the effectiveness of a dental health education intervention in enhancing toothbrushing independence among school students in Banda Aceh. A quasi-experimental design with pre-test and post-test assessments was employed, involving 87 students selected through purposive sampling. Data were collected using an observation form and analyzed using univariate analysis and the Wilcoxon test. The results revealed that before the intervention, 58.6% of respondents were partially independent in tooth brushing, while only 21.8% were entirely independent. After the intervention, the number of independent children increased by 94.7%, and the non-independent category decreased by 35.3%. The Wilcoxon test showed a statistically significant difference in tooth brushing independence before and after the intervention (Z=-3.55, p=0.0004). The findings highlight the importance of practical education in equipping children with the necessary skills to maintain oral health. Developing a comprehensive Dental Care Nursing Service Model integrating innovative educational methods and involving parents and teachers is recommended to foster sustainable, healthy habits among school students in Banda Aceh.